IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY (CSR) AND CSR ACCOUNTING TREATMENT ON FINANCIAL PERFORMANCE OF MULTINATIONAL COMPANIES - Annisa Rahma Qur’aini; Via Wahyuningtyas; Hwihanus (Jurnal Media Akademik (JMA), 2024)
This study explores the implementation of Corporate Social Responsibility (CSR) practices and their accounting treatment on the financial performance of multinational companies (MNCs). It investigates how MNCs incorporate CSR initiatives into their operations and how these initiatives are accounted for in financial reporting. The study analyzes the impact of CSR implementation and accounting treatment on various financial performance indicators of MNCs. The research aims to provide insights into the relationship between CSR practices, accounting treatment, and financial performance, contributing to the existing literature on CSR and corporate finance.